Renewable materials and green technology products : environmental and safety aspects - Kulkarni, Shrikaant; Abraham, Ann Rose; Haghi, A. K. (Palm Bay, FL, USA ; Burlington, ON, Canada : Apple Academic Press ; Boca Raton, FL, USA ; Abingdon, Oxon, UK : CRC Press, 2021)
"Renewable Materials and Green Technology Products: Environmental and Safety Aspects looks at the design, manufacture, and use of efficient, effective, safe, and more environmentally benign chemical products and processes. It includes a broad range of application-based solutions to the development of renewable materials and green technology. The latest trends in the green synthesis and properties of CNs are presented in the first chapter of this book for generating social awareness about sustainable developments. The book goes on to highlight the naissance and progressive trail of microwave-assisted synthesis of metal oxide nanoparticles, for a clean and green technology tool. Chapters discuss green technological alternatives for the global abatement of air pollution, effective use and treatment of water and wastewater, renewable power generation from solar PV cells, carbon-based nanomaterials synthesized using green protocol for sustainable development, green technologies that help to achieve economic development without harming the environment, technical solutions to cut down the quantum of N losses, conventional processing techniques in developing the bionanocomposites as the biocatalyst, and more."--
Green Synthesized Carbon-Based Nanomaterials: Synthesis and Properties / Binila K Korah, Neena John Plathanam, Anu Rose Chacko, Mamatha Susan Punnoose, Thomas Abraham, and Beena Mathew -- Microwave-Assisted Synthesis: A New Tool in Green Technology / Sreerenjini C. R., Bhagyalakshmi Balan, Gladiya Mani, and Suresh Mathew -- Global Abatement of Air Pollution Through Green Technology Routes / Sijo Francis, Remya Vijayan, Ebey P. Koshy, and Beena Mathew -- Application of Green Technology in Water and Wastewater Treatments / Remya Vijayan, Sijo Francis, and Beena Mathew -- Green Energy: Renewable Power Generation from Solar PV Cells / M. A. Asha Rani, M. Chakkarapani, and Pranjit Barman -- Green Synthesized Carbon-Based Nanomaterials: Applications and Future Developments / Anu Rose Chacko, Neena John Plathanam, Binila K Korah, Thomas Abraham, and Beena Mathew -- Development of Green Technology Through Renewable and Sustainable Materials / Remya Vijayan, Sijo Francis, and Beena Mathew -- Green Technologies for Nutrient Cycles in Crop and Livestock Systems Management / Shrikaant Kulkarni -- Bionanocomposite Materials and Their Applications / Shrikaant Kulkarni -- A Study on Magnetic Metal Carbon Mesocomposites Green Synthesis Peculiarities with Point of Chemical Mesoscopics View / V. I. Kodolov, V. V. Kodolova-Chukhontzeva, N. S. Terebova, and I. N. Shabanova -- The Role of Nanostructure Activity in Selected Green Material Modification / V. I. Kodolov, V. V. Kodolova-chukhonseva, Yu V. Pershin, R. V. Mustakimov,G. I. Yakovlev, and A. Yu. Bondar.
OCLC-licensed vendor bibliographic record.
Keywords: Green technology; Nanostructured materials; Nanotechnology -- Environmental aspects; Green chemistry; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Environmental Science; SCIENCE / Chemistry / General